Sistem Pakar Diagnosa Penyakit Tanaman Bawang Merah Menggunakan Metode Certainty Factor - Mohammad Fathor Rosi; Bakhtiyar Hadi Prakoso (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2020)
The lack of knowledge of farmers and the unequal counseling about onion diseasefrom experts is a strong reason for the difficulty of overcoming or immediately treateddiseases of onions, for this requires early diagnosis of disease onion plants. Thisresearch uses the Certainty Factor method. This method uses the certainty of an experton the symptoms of each disease. By determining the value of MB (Measure ofBelieve) as the level of confidence in the hypothesis and MD (Measure of Disbelieve)the level of distrust of the hypothesis. After using the Certainty Factor formula, thevalue of each disease will be generated from the new symptoms owned by using thehighest value of each disease, so that is the result of disease diagnosis in shallots. Thisstudy uses as many as 35 data as testing and from these data obtained an accuracyvalue of 85.71%